Risk factors for Drug-resistant of Gram-negative Bloodstream Infection in Patients with Hematological Malignancies. (4th October 2017) - Brufman, Tamar; Ram, Ron; Avivi, Irit; Ben-Ami, Ronen
Abstract: Background: Bloodstream infections (BSI) are significant causes of morbidity and mortality in patients with hematological malignancies. Antimicrobial resistance may be increasing among Gram-negative bacteria in this population, with implications for empirical treatment and preventive strategies. Methods: We performed a retrospective study of patients with hematological malignancies and Gram-negative bacillus bloodstream infection (GNB-BSI) at the Tel Aviv Medical Center, a 1, 200-bed teaching hospital, from 2009 through 2015. Bacteremia was defined as breakthrough if the patient received >48 hours of systemic antibiotic treatment at the time of culture. Patient demographics, disease status and antimicrobial exposure within the previous 90 days were analyzed as potential risk factors for drug-resistant GNB-BSI using bivariate analyses and logistic regression. Results: Three-hundred thirteen episodes of GNB-BSI occurred in 198 patients during the study period. Enterobacteriaceae accounted for 236 (75%) episodes ( E. coli, n = 117; Klebsiella pneumoniae, n = 92; 35% ESBL producers) and nonfermenters accounted for 71 (22%) episodes. Susceptibility rates were: Piperacillin/Tazobactam, 75%; Ceftazidime, 66%; Ciprofloxacin, 68%; and Imipenem, 93%. Medical tourism was associated with GNB-ESBL infection (odds ratio 1.5; P = 0.03). Neutropenia and breakthrough infection were risk factors for resistance to Piperacillin/Tazobactam (OR 2.1; P = 0.02). The use of quinolones prophylactically was associated with resistance to ciprofloxacin (OR 2.0; P = 0.002) but not to other agents. Breakthrough GNB-BSI was associated with 35% carbapenem resistance (OR 7.8; P < 0.0001). Crude 30-day mortality was 27.9%. Resistance to carbapenems was the only independent predictor of death (OR 2.3, P = 0.0008). Conclusion: Breakthrough infection was the dominant risk factor for resistant GNB-BSI, and was linked with significantly increased mortality. Resistance rates to most first-line antibiotics were high, suggesting that a policy of deescalation should be considered. Disclosures: All authors: No reported disclosures.